2014
DOI: 10.1371/journal.pone.0097050
|View full text |Cite
|
Sign up to set email alerts
|

Alona iheringula Sinev & Kotov, 2004 (Crustacea, Anomopoda, Chydoridae, Aloninae): Life Cycle and DNA Barcode with Implications for the Taxonomy of the Aloninae Subfamily

Abstract: Knowledge of reproductive rates and life cycle of the Cladocera species is essential for population dynamic studies, secondary production and food webs, as well as the management and preservation of aquatic ecosystems. The present study aimed to understand the life cycle and growth of Alona iheringula Kotov & Sinev, 2004 (Crustacea, Anomopoda, Chydoridae), a Neotropical species, as well as its DNA barcoding, providing new information on the Aloninae taxonomy. The specimens were collected in the dammed portion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…An extensive DNA barcode study on Microgastrinae wasps demonstrated significant insights into their taxonomy and species discovery [22]. Such cryptic diversity has been uncovered using DNA barcodes in other animal taxa, including crustaceans, diatoms, and fish [23][24][25]. The use of DNA barcodes for the discovery of new species is emerging as a powerful tool to clarify species boundaries and to quantify species diversity [26].…”
Section: Box 1 Building the Dna Barcode Library Using Sanger Sequencingmentioning
confidence: 99%
“…An extensive DNA barcode study on Microgastrinae wasps demonstrated significant insights into their taxonomy and species discovery [22]. Such cryptic diversity has been uncovered using DNA barcodes in other animal taxa, including crustaceans, diatoms, and fish [23][24][25]. The use of DNA barcodes for the discovery of new species is emerging as a powerful tool to clarify species boundaries and to quantify species diversity [26].…”
Section: Box 1 Building the Dna Barcode Library Using Sanger Sequencingmentioning
confidence: 99%
“…The egg production of A. guttata is similar to other species of Chydoridae, as seen in Table 2. The longevity of A. guttata (30,9 days) is higher to those of other species of Chydoridae Santos Silva et al, 2014). Many factors can influence cladocerans longevity, especially water temperature, photoperiod and food quality Ferrão-Filho and Azevedo, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Classic taxonomy and geographic distribution of Cladocera in general date from nineteen century throughout the Americas, but only only recently (last fifty years) changed to be devoted to studies on life cycle, particularly the reproductive parameters of species and recently intensified to explore the genetic material (Silva et al, 2014;Castilho et al, 2015;Abreu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, biomass quantification studies and secondary production of aquatic populations and communities provide information on the organic matter available at different trophic levels and can characterize the complexity of the main biotic interactions, such as competition, predation and natural disturbances (Echevarría et al, 1990;Ahrens & Peter, 1991). Cultivation under controlled conditions allows a detailed observation of individuals' development and a better understanding of several bionomical aspects, such as body growth, reproduction and longevity (Silva et al, 2014). These data can be used to select species to be used as test organisms or as indicators in environmental quality studies, thus contributing to the management and preservation of aquatic environments (Adema, 1978;Freitas & Rocha, 2006;Mansano et al, 2018).…”
Section: Introductionmentioning
confidence: 99%